Perancangan Sistem Informasi Pendataan Tahanan Berbasis Web Menggunakan Framework Laravel pada Badan Narkotika Nasional Provinsi Sumatera Selatan - Danisa Enjelika; Diana Diana (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
This internship was carried out at the South Sumatra Provincial Narcotics National Agency (BNNP Sumatera Selatan), specifically in the Eradication and Intelligence Division. The internship identified problems in inmate data management, where the process was still handled manually and partly using Microsoft Excel, resulting in difficulties in searching, updating, and reporting data. To solve this issue, a web-based inmate data information system was developed using the Laravel framework and MySQL database. The system was designed with several key features, including user login, dashboard, inmate data management, inmate history, photo upload, data search, status filtering, and user profile management. The development process included problem analysis, system requirements analysis, system design using use case diagrams, activity diagrams, and ERD, implementation, and black box testing. The test results showed that all main functions worked properly according to the expected requirements. Therefore, the system can support inmate data management in a more structured, efficient, and effective way.